Altered oscillatory cerebral blood flow velocity and autoregulation in postural tachycardia syndrome - Medow, Marvin S.; Del Pozzi, Andrew T.; Messer, Zachary R.; Terilli, Courtney; Stewart, Julian M. (Frontiers in Physiology, 2014)
Decreased upright cerebral blood flow (CBF) with hyperpnea and hypocapnia is seen in a minority of patients with postural tachycardia syndrome (POTS). More often, CBF is not decreased despite upright neurocognitive dysfunction. This may result from time-dependent changes in CBF. We hypothesized that increased oscillations in CBF occurs in POTS (N=12) compared to healthy controls (N=9), and tested by measuring CBF velocity (CBFv) by transcranial Doppler ultrasound of the middle cerebral artery, mean arterial pressure (MAP) and related parameters, supine and during 70o upright tilt. Autospectra for mean CBFv and MAP, and transfer function analysis were obtained over the frequency range of 0.0078 to 0.4 Hz. Upright HR was increased in POTS (125±8 vs 86±2 bpm), as was diastolic BP (74±3 vs 65±3 mmHg) compared to control, while peripheral resistance, cardiac output, and mean CBFv increased similarly with tilt. Upright BP variability (BPV), low frequency (LF) power (.04 - 0.13 Hz) , and peak frequency of BPV were increased in POTS (24.3±4.1, and 18.4±4.1 mmHg2/Hz at .091 Hz vs 11.8±3.3, and 8.8 ± 2 mmHg2/Hz c at 0.071 Hz), as was upright overall CBFv variability, low frequency power and peak frequency of CBFv variability (29.3±4.7, and 22.1±2.7 [cm/s]2/Hz at .092 Hz vs 14.7±2.6, and 6.7 ± 1.2 [cm/s]2/Hz at 0.077Hz). Autospectra were sharply peaked in POTS. LF phase was decreased in POTS (-14 ± 4 vs -25 ± 10 degrees) while upright. LF gain was increased (1.51 ± 0.09 vs 0.86 ± 0.12 [cm/s]/ mmHg) while coherence was increased (0.96 ± 0.01 vs 0.80 ± 0.04). Increased oscillatory BP in upright POTS patients is closely coupled to oscillatory CBFv over a narrow bandwidth corresponding to the Mayer wave frequency. Therefore combined increased oscillatory BP and increased LF gain markedly increases CBFv oscillations in a narrow bandwidth. This close coupling of CBF to MAP indicates impaired cerebral autoregulation that may underlie upright neurocognitive dysfunction in POTS.